2008
DOI: 10.1161/circresaha.108.178970
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3 Inhibition Slows Mitochondrial Adenine Nucleotide Transport and Regulates Voltage-Dependent Anion Channel Phosphorylation

Abstract: Abstract-Inhibition of glycogen synthase kinase (GSK)-3 reduces ischemia/reperfusion injury by mechanisms that involve the mitochondria. The goal of this study was to explore possible molecular targets and mechanistic basis of this cardioprotective effect. In perfused rat hearts, treatment with GSK inhibitors before ischemia significantly improved recovery of function. To assess the effect of GSK inhibitors on mitochondrial function under ischemic conditions, mitochondria were isolated from rat hearts perfused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(186 citation statements)
references
References 41 publications
6
180
0
Order By: Relevance
“…To confirm that the dysregulation of cAMP production in the KO mouse was due to a direct effect of deletion of Gsk3a, we used SB415286, a relatively selective, small molecule inhibitor of GSK-3 (25,26). Pretreatment of WT cardiomyocytes for 30 minutes with SB415286 led to a significant reduction in the contractile response to isoproterenol, mimicking the findings in the KO cells ( Figure 8C).…”
Section: Figuresupporting
confidence: 55%
“…To confirm that the dysregulation of cAMP production in the KO mouse was due to a direct effect of deletion of Gsk3a, we used SB415286, a relatively selective, small molecule inhibitor of GSK-3 (25,26). Pretreatment of WT cardiomyocytes for 30 minutes with SB415286 led to a significant reduction in the contractile response to isoproterenol, mimicking the findings in the KO cells ( Figure 8C).…”
Section: Figuresupporting
confidence: 55%
“…GSK-3b inhibition), which protects the adult-rat heart from I/R injury for 2-4 h. 4,[13][14][15][16] This study showed a link between the Zn 2 þ i release/increase and the activation of GSK-3b, resulting in myocyte apoptosis. We observed an early increase in p-Ser9 GSK-3b levels after Zn 2 þ Figure S2b), we conclude that Zn 2 þ i supplementation-induced early phosphorylation at Ser9 is not necessarily cardioprotective and may induce cytotoxicity after return to normal medium for 4 or 24 h. In support of the above conclusions, Tyr216 phosphorylation is required for nuclear GSK-3b accumulation in neurons and fibroblasts, 17,18 as mutation of Tyr216 to phenylalanine or its dephosphorylation results in less GSK-3b being found in nuclei.…”
Section: Discussionmentioning
confidence: 67%
“…When the reperfusion injury salvage kinase (RISK) family members PKA, PKB/Akt, PKC, and MEK-ERK are activated by pre-or post-conditioning, a common downstream protein, GSK-3b, is phosphorylated at Ser9, resulting in GSK-3b inhibition (both events occurring within 20 min of the end of conditioning), leading to the inhibition of mPTPs and the salvaging of 20-50% live myocardium. 4,5,[13][14][15][16] A potent GSK-3 inhibitor, SB216763 (SB21), 4,13 had a relatively weak protective effect against H 2 O 2 -, ONOO À -induced myocyte death (Supplementary Figure S2c), but gave better protection against 10 mM Zn 2 þ -induced cell toxicity at 4 h (Figure 2d (TUNEL test) were performed as follows: after ischemia for 40 min, followed by reperfusion for 4 h, myocytes were returned to normal medium without inhibitors for 24 h, then were examined for apoptotic markers. Compared with I/R alone ('I/R', Figure 4b), the presence of 15 mM TPEN at the start of reperfusion for only B20 min ('TPEN (20 min)') markedly inhibited I/R injury at 24 h after TPEN removal, suggesting that the reperfusion-induced initial Zn 2 þ i release (Figure 3b) is important in I/R injury.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the impact of charge modification on VDAC channel function has been shown previously as VDAC treatment with succinic anhydride, which increases the negative charge of the channel, eliminates VDAC voltage-dependence and changes its selectivity from anion to cation (79). Further, VDAC phosphorylation leading to increased negative charge was shown to decrease the conductance of the channel, though the modified residue(s) were not identified (80,81). It is also possible that the association of VDAC with modulatory proteins is altered when VDAC is succinated; an increase in the negative charge of the protein could e.g.…”
Section: Protein Succination In Leigh Syndromementioning
confidence: 95%